Building Intuition Insights From Basic Operations Management Models and Principles - Chhajed, Dilip; Lowe, Timothy J.; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
One of the primary purposes of any model is to build intuition and generate insights. Typically, a model is developed to be able to better understand phenomena that are otherwise difficult to comprehend. Models can also help in verifying the correctness of an intuition or judgment. In spite of the fact that many educators and practitioners recognize the intuition-building power of simple models, this is the first book in the field that uses the power of the basic models and principles to provide students and managers with an (3z(Bintuitive understanding(3y (Bof operations management. Building Intuition: Insights From Basic Operations Management Models and Principles touches on nine fundamental models and principles, and outlines the key insights behind each one. To ensure that the volume is accurate, authoritative, accessible and well-written, the chapters are developed by leading experts in each chapter area and written with the students and managers in mind. The book$1 (Bs primary purpose is to motivate and to enable readers to develop insights with respect to a number of models that are central to the study and practice of operations management. .s
Sequencing: The Shortest Processing Time Rule -- The Knapsack Problem -- Flexibility Principles -- Single Server Queueing Models -- Little's Law -- The Median Principle -- The Newsvendor Problem -- The Economic Order-Quantity (EOQ) Model -- Risk Pooling.
Keywords: Business; Management science; Management; Production management; Operations research; Decision making; Mathematical models; Business and Management; Operation Research/Decision Theory; Management; Mathematical Modeling and Industrial Mathematics; Operations Research, Management Science; Operations Management; Business and Management, general; Electronic books